Risk aversion and schooling decisions - Christian Belzil; Marco Leonardi (Institute for the Study of Labor (IZA), 2007)
We develop a non-rational expectation econometric model of sequential schooling decisions. Using unique Italian panel data in which individual differences in attitudes toward risk are measurable (with error), we investigate the effect of risk aversion on the probability of entering higher education. This allows us to characterize the subjective (as opposed to the objective) effect of higher education on marginal risk exposure. Because the measure of risk aversion (the classical Arrow-Pratt degree of absolute risk aversion) is posterior to schooling decisions, it depends on current wealth realizations and we must therefore take into account its endogeneity. We also allow risk aversion to be measured with error. After taking into account both the endogeneity of wealth and measurement error, we find that risk aversion is a key determinant (comparable to parents' educational background) of the decisions to enter higher education. Precisely, risk aversion acts as a deterrent to higher education investment.
Keywords: 330; Bildungsverhalten; Risikoaversion; Studium; Italien